Developing undergraduate autism education for medical students: a qualitative study - Sube Banerjee; Juliet Wright; Ann White; Stephanie Daley; Yvonne Feeney; Yasmin Dhuga; Laura Gallaher (BMJ Publishing Group, 2022)
Background Autistic adults and children experience considerable health inequalities and have high rates of premature mortality, hospital admissions and emergency department visits. This is in part due to a lack of autism awareness in the healthcare and social care workforce. A new educational programme, Time for Autism (TfA), for medical students is being developed to address this challenge. This qualitative study was undertaken to support the development of the new programme in order to (1) understand the medical care experiences of parents of autistic children and (2) assess their views on the acceptability of the new TfA programme and willingness to be involved.Methods A convenience sample of 11 parents of autistic children were recruited across the South of England. The ages of the autistic children ranged from 3 to 17 years. Semistructured interviews were completed between October and December 2019. Interview transcripts were analysed using thematic analysis.Results Three key themes were identified: diagnosis, experiences of doctors and TfA considerations. There was support for and willingness to take part in a dedicated autism education programme for medical students, and constructive feedback to inform and improve its delivery.Conclusion The findings from this study provide insights into the medical care experiences of parents/carers of autistic children. Understanding how parents/carers of autistic children would like medical care to be improved can be used to develop TfA and other autism programmes. Parental/carer support for the development of and involvement in an autism medical education programme enhances the feasibility of the new programme.